Comparison of the mechanical properties of the anterior lens capsule in senile cataract, senile cataract with trypan blue application, and pseudoexfoliation syndrome. Issue 8 (August 2017) - Simsek, Cem; Oto, Sibel; Yilmaz, Gursel; Altinors, Dilek Dursun; Akman, Ahmet; Gungor, Sirel Gur
Abstract : Purpose : To evaluate the elastic modulus, hardness, and mechanical properties of the anterior lens capsule in different types of cataract and to assess the correlation with age. Setting : Baskent University Hospital, Department of Ophthalmology, Ankara, Turkey. Design : Prospective comparative study. Methods : Patients were divided into 3 groups. Group 1 comprised patients with senile cataract, Group 2 patients had pseudoexfoliation (PXF) syndrome, and Group 3 patients had dye‐enhanced cataract surgery. The capsules were analyzed using a nanoindentation device. Young's modulus of elasticity was measured by the Oliver‐Pharr method and capsule hardness by the Martens method. Results : The study comprised 72 patients, 24 per group. The mean Young's modulus was 7.53 GPa ± 1.07 (SD) in Group 1, 6.01 ± 1.25 GPa in Group 2, and 8.12 ± 0.98 GPa in Group 3. The capsules in Group 2 were more elastic than in Group 1 and Group 3 ( P < .001). The capsules in Group 3 had lower elasticity than in Group 1, although the difference was not significant ( P = .94). The mean capsule stiffness was 326.41 ± 98.40 MPa in Group 1, 210.5 ± 52.32 MPa in Group 2, and 315.54 ± 163.15 MPa in Group 3. The lens capsules in Group 2 were less stiff than those in Group 1 and Group 3 ( P < .001). Conclusions : Capsule thickness was positively correlated with increasing age in all groups. The anterior lens capsules of patients with PXF had more elasticity and less stiffness than the other groups. Intracameral trypan blue application had no effect on capsule elasticity and stiffness.